2019
DOI: 10.3390/molecules24193498
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eight Novel Spiroleptosphols from Fusarium avenaceum

Abstract: Chemical analyses of Fusarium avenaceum grown on banana medium resulted in eight novel spiroleptosphols, T1, T2 and U–Z (1–8). The structures were elucidated by a combination of high-resolution mass spectrometric data and 1- and 2-D NMR experiments. The relative stereochemistry was assigned by 1H coupling and NOESY/ROESY experiments. Absolute stereochemistry established for 7 by vibrational circular dichroism was found analogous to that of the putative polyketide spiroleptosphol from Leptosphaeria doliolum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The relative stereochemistry was assigned using 1 H NMR coupling constants, NOESY, and ROESY experiments, while the AC was established as (6 R ,9 S ,10 R ,11 R ,12 R ,13 S )− 188 by VCD. 90…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative stereochemistry was assigned using 1 H NMR coupling constants, NOESY, and ROESY experiments, while the AC was established as (6 R ,9 S ,10 R ,11 R ,12 R ,13 S )− 188 by VCD. 90…”
Section: Resultsmentioning
confidence: 99%
“…The relative stereochemistry was assigned using 1 H NMR coupling constants, NOESY, and ROESY experiments, while the AC was established as (6R,9S,10R,11R,12R,1 3S)−188 by VCD. 90 VCDEC was used to determine the (2R,2'R,3S) absolute stereochemistry at C-2' in 189 ( Figure 50) using the mono (S)-MTPA ester of chaetophenol G isolated from Chaetomium cancroideum. 91 The structure of (-)-aloesaponol III 8-methyl ether (190) (Figure 51), isolated from the roots of Eremurus persicus, was elucidated by IR and NMR experiments and the AC was assigned through VCD and ECD spectroscopies as (R).…”
Section: Polyketidesmentioning
confidence: 99%
“…Gunatilaka et al employed this mechanism to explain the reasons behind the inseparable diastereomers of oxaspirol B . Furthermore, Wimmer et al reported the ring-opened analog spiroleptosphol V from Fusarium avenaceum , corresponding to the right structure in Scheme . We assumed that this mechanism contributes to the generation of C-6 diastereomers 1 and 2 , as described in the next section.…”
Section: Resultsmentioning
confidence: 99%